Niat Perilaku Pengguna terhadap Layanan Peer-to-peer (P2P) Lending Syariah - Yudi Febrianda (Journal of Innovative and Creativity, 2025)
This study aims to analyse the factors that influence users' behavioural intention towards Islamic Peer-to-Peer (P2P) Lending services. This study uses the Technology Acceptance Model (TAM) to understand how psycho-social and technical variations affect users' decisions to use Islamic P2P lending services. In this study, four independent variables were explored, namely Perceived usefulness, perceived ease of use, attitude and Consumer Trust. Data was collected through an online survey using Google Form and analysed using Structural Equation Modeling (SEM) technique. A total of 269 respondents from Pekanbaru City and Kampar Regency. The results showed Perceived usefulness, perceived ease of use and attitude have a positive and significant influence on Behavioural Intention. While Consumer Trust has no effect on Behavioural Intention. This research makes a significant contribution in understanding the dynamics of using Islamic financial technology and can be used by fintech platforms to improve service effectiveness.